Single-walled carbon nanotubes oust graphene and semiconductor saturable absorbers in Q-switched solid-state lasers at 2 µm. (22nd August 2017) - Mateos, Xavier; Loiko, Pavel; Choi, Sun Young; Rotermund, Fabian; Aguiló, Magdalena; Díaz, Francesc; Griebner, Uwe; Petrov, Valentin
Abstract: The superior performance of a saturable absorber (SA) based on randomly-oriented single-walled carbon nanotubes (SWCNTs) operating in the spectral region of their first fundamental transition E 11 over a graphene-SA containing several ( n = 3) carbon layers and a commercial semiconductor SA (SESA) for passive Q -switching of bulk thulium solid-state lasers is demonstrated. Using SWCNT-SA in a compact diode-pumped Tm:KLuW laser, a maximum average output power of 1.36 W is achieved at 1932–1944 nm corresponding to a slope efficiency of 41% and pulse characteristics of 48 ns/5.5 µ J which are superior to that for graphene-SA (123 ns/3.1 µ J) and SESA (61 ns/1.1 µ J). SWCNT-SAs are promising for eye-safe miniature lasers at 2 µ m generating nanosecond pulses in the MHz repetition frequency range.